Documentation and valuation of plant resources used by the Orang Asli at Kampung Lubuk Ulu Legong, Baling, Kedah / Nur Shahidah Binti Mohammad - Nur Shahidah, Mohammad (2014)

(untitled)
This study was carried out to identify, characterize and valuate the plant resource used by the Orang Asli in Kampung Lubuk Ulu Legong, Baling, Kedah. The data for this study was collected through home garden plants survey, wild plant survey and structured interviews with the villagers. During this study a total of 175 plants species were encountered of which 68 species were cultivated, 91 species were wild and 16 species were both cultivated and wild. Among the cultivated plants the family Euphorbiaceae recorded the highest number of species. Among the wild plants, the family Arecaceae recorded the highest number of species. Most of the plant species were used as a food. Income, medicinal, ornamental, handcraft making, utensil, fish poisoning and belief were respectively second, third, fourth, fifth, sixth and seventh in term of number of species. 29.7% of the total of species was multi-purpose and 70.3% have a single use. The most common part of plant used was fruit. This is followed by whole plants, leaves, roots, stem, latex, rhizomes, bark, shoots and flowers. In term of Use-Value index, species Nephelium lappaceum L. and Chasalia chartacea Craib have the highest value. Among species with high use-value, Bambusa ventricosa McClure considered the most frequently used. Species with the highest medicinal importance value (Iv) was Cinnamomum iners Reinw. ex Blume. Estimated annual income generated from plant resource was Malaysian Ringgit 505,750.00 per year for the whole village. Species that contributed most to the income was Hevea brasiliensis Muell. Arg. followed by Aquilaria malaccensis Lamk. and Calamus conirostris Becc.